Structural and Functional Analysis of a Novel Coiled-Coil Protein Involved in Ypt6 GTPase-regulated Protein Transport in Yeast - Tsukada, Miki (The American Society for Cell Biology, 1999)
The yeast transport GTPase Ypt6p is dispensable for cell growth and secretion, but its lack results in temperature sensitivity and missorting of vacuolar carboxypeptidase Y. We previously identified four yeast genes (SYS1, 2, 3, and 5) that on high expression suppressed these phenotypic alterations. SYS3 encodes a 105-kDa protein with a predicted high α-helical content. It is related to a variety of mammalian Golgi-associated proteins and to the yeast Uso1p, an essential protein involved in docking of endoplasmic reticulum–derived vesicles to the cis-Golgi. Like Uso1p, Sys3p is predominatly cytosolic. According to gel chromatographic, two-hybrid, and chemical cross-linking analyses, Sys3p forms dimers and larger protein complexes. Its loss of function results in partial missorting of carboxypeptidase Y. Double disruptions of SYS3 and YPT6 lead to a significant growth inhibition of the mutant cells, to a massive accumulation of 40- to 50-nm vesicles, to an aggravation of vacuolar protein missorting, and to a defect in α-pheromone processing apparently attributable to a perturbation of protease Kex2p cycling between the Golgi and a post-Golgi compartment. The results of this study suggest that Sys3p, like Ypt6p, acts in vesicular transport (presumably at a vesicle-docking stage) between an endosomal compartment and the most distal Golgi compartment.